2017
DOI: 10.1155/2017/3068548
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Fault Diagnosis Method for Power Transformers Using Modified Kriging Model

Abstract: A data-driven fault diagnosis method that combines Kriging model and neural network is presented and is further used for power transformers based on analysis of dissolved gases in oil. In order to improve modeling accuracy of Kriging model, a modified model that replaces the global model of Kriging model with BP neural network is presented and is further extended using linearity weighted aggregation method. The presented method integrates characteristics of the global approximation of the neural network techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Jia et al found that Kriging interpolation can better reflect the spatial distribution characteristics of the target region, but the accuracy of neural network interpolation is higher [31]. In [32], an improved model using BP neural network technology instead of Kriging global model is proposed, which is further extended by linear weighted aggregation method to improve the modeling accuracy. Katsuaki et al proposed a neural Kriging interpolation method, which reproduces the spatial characteristics of regionalized variables and improves the interpolation accuracy to some extent in [33].…”
Section: Related Workmentioning
confidence: 99%
“…Jia et al found that Kriging interpolation can better reflect the spatial distribution characteristics of the target region, but the accuracy of neural network interpolation is higher [31]. In [32], an improved model using BP neural network technology instead of Kriging global model is proposed, which is further extended by linear weighted aggregation method to improve the modeling accuracy. Katsuaki et al proposed a neural Kriging interpolation method, which reproduces the spatial characteristics of regionalized variables and improves the interpolation accuracy to some extent in [33].…”
Section: Related Workmentioning
confidence: 99%